Pengaruh Kualitas Layanan Terhadap Loyalitas Pelanggan dalam Industri Jasa Pengiriman - Daffa Fawwas Al Hafizh; Anak Agung Ketut Diatmika (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The use of delivery services in Indonesia is increasing, leading to intense competition among companies such as J&T Express, JNE, SICEPAT, and SPX. This study aims to examine the relationship between service quality, customer satisfaction, and customer loyalty among J&T Express users in Tangerang Regency. The results indicate that service quality has a significant impact on customer satisfaction. High customer satisfaction increases the likelihood of repeat service use and fosters stronger customer loyalty. The study supports the theory that service quality is crucial in building customer satisfaction and loyalty. It is recommended that J&T Express focus on improving service quality to retain and attract new customers. The study has limitations, such as a sample size that may not represent the broader population and potential bias in data collection. Future studies are suggested to conduct longitudinal research and explore other variables that may influence the relationship between these variables. This research employs a descriptive causal design with a quantitative approach and uses purposive sampling techniques. Data were collected from 123 respondents who are J&T users. Data analysis was performed using Partial Least Square-Structural Equation Modelling (PLS-SEM). The research findings reveal that service quality has a positive effect on customer satisfaction, service quality positively affects customer loyalty, and customer satisfaction positively impacts customer loyalty.